Evolution of Calpurnia Tate - Kelly, Jacqueline (New York Square Fish, 2011)
In central Texas in 1899, eleven-year-old Callie Vee Tate is instructed to be a lady by her mother, learns about love from the older three of her six brothers, and studies the natural world with her grandfather.
Originally published: New York : Henry Holt, 2009. Newberry Honor Book.
Includes discussion questions.
830L
100326
Keywords: Darwin, Charles -- 1809-1882.; Nature; Family life -- Texas; Grandfathers; Naturalists; Families; Technology -- Social aspects; Texas -- Social life and customs -- 19th century; Texas -- History -- 19th century; Bildungsromans